Weed seed decay in conventional and diversified cropping systems. (17th October 2013) - Gómez, R; Liebman, M; Munkvold, G; Storkey, Jonathan
Summary Diversified cropping systems can have high soil microbial biomass and thus strong potential to reduce the weed seedbank through seed decay. This study, conducted in Iowa, USA, evaluated the hypothesis that weed seed decay is higher in a diversified 4‐year maize–soyabean–oat/lucerne–lucerne cropping system than in a conventional 2‐year maize–soyabean rotation. Mesh bags filled with either Setaria faberi or Abutilon theophrasti seeds and soil were buried at two depths in the maize phase of the two cropping systems and sampled over a 3‐year period. Setaria faberi seed decay was consistently greater at 2 cm than at 20 cm burial depth and was higher in the more diverse rotation than in the conventional rotation in 1 year. Abutilon theophrasti seeds decayed very little in comparison with seeds of S. faberi. Separate laboratory and field experiments confirmed differences in germination and seed decay among the seed lots evaluated each year. Fusarium, Pythium, Alternaria, Cladosporium and Trichoderma were the most abundant genera colonising seeds of both species. A glasshouse experiment determined a relationship between Pythium ultimum and S. faberi seed decay. Possible differences in seed susceptibility to decay indicate the need to evaluate weed seedbank dynamics in different cropping systems when evaluating overall population dynamics and formulating weed management strategies.